Ageing accounts for much of the association between decreasing grip strength and subsequent loneliness: the English Longitudinal Study of Ageing. Issue 3 (7th March 2022) - Vingeliene, Snieguole; Hiyoshi, Ayako; Lentjes, Marleen; Fall, Katja; Montgomery, Scott
Abstract : Background: Loneliness at older ages has been associated with higher morbidity and mortality. One of the risk factors for loneliness may be age-related decline in skeletal muscle strength, which may limit the possibilities for engagement in usual social activities and maintaining relationships. We aimed to identify if decrease in grip strength is an independent determinant of subsequent change in loneliness. Methods: Prospective cohort study of participants aged 50 years or older living in private households and provided data in the English Longitudinal Study of Ageing waves 2 (2004/2005), 4 (2008/2009) and 6 (2012/2013) (n=6118). We used fixed effects linear models to estimate β coefficients and 95% confidence intervals. Results: The adjusted estimates for a 5-kilogramme decrease in grip strength and loneliness score (ranging from 3 to 9) are β 0.04 and 95% CI −0.003 to 0.08 among men and β 0.03 and 95% CI −0.02 to 0.09 among women. In age-stratified analysis, a statistically significant association was observed among men below the age of 80 years (0.04, 0.0001 to 0.08) but not among older men (0.04, –0.28 to 0.35), and among women below the age of 80 years (0.03, –0.002 to 0.09) or above (−0.02, –0.32 to 0.28). Conclusion: Muscle strength declines with age and may help explain the greater social isolation that occurs at older ages. Decline in strength was only independently associated with modestly increased loneliness among men younger than 80 years of age, indicating its limitation as a potential marker of loneliness risk.